Projeto preliminar de equipamento para elevação de automóveis - Fernandes, André Cefas de Souza (Universidade Federal Rural do Semi-Árido, 2019)
Large urban centers are constantly suffering from the problem of the growing number of vehicles on the road. This makes it necessary to think of new ways to organize them. The present work launches a proposal of a device design that will facilitate the organization of vehicles in parking spaces, capable of lifting the cars so that these can be stored more efficiently. Following design methodologies to validate the sizing of the components through the calculation memorial in spreadsheets along with drawings and simulations in computer software. With this, it was possible to carry out the sizing of the main components and to study their integrity through simulations, where it was verified that certain components need to be redesigned.
Monografia
Keywords: Automação; Macaco mecânico; Metodologias de projeto; Simulações; Comportamentos; Dimensionamento; Automation; Mechanical monkey; Project methodologies; Simulations; Behaviors; Sizing; ENGENHARIAS::ENGENHARIA MECANICA